2022
DOI: 10.3390/life12081157
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Group in Relation to COVID-19 Susceptibility and Clinical Outcomes: A Retrospective Observational Study in the United Arab Emirates

Abstract: (1) Background: The association between ABO blood groups and COVID-19 outcomes was investigated in several studies. The results were controversial. This study aimed to explore the association between ABO blood groups and COVID-19 outcomes. (2) Methods: This retrospective study included 303 COVID-19 patients treated at the NMC Royal Hospital in the United Arab Emirates between 8 April 2020 and 30 June 2020. (3) Results: The mean age of patients included in the study was 39.3 ± 10.7 years, and 72.9% of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
4
1
Order By: Relevance
“…Additionally, some studies have analyzed rhesus factor (Rh) associations with COVID-19 severity as well [10,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some studies have analyzed rhesus factor (Rh) associations with COVID-19 severity as well [10,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some studies have analyzed rhesus factor (Rh) associations with COVID-19 severity as well [ 10 , 16 - 20 ]. Our study first demonstrates that ABO blood groups alone do not have an influence on COVID-19 mortality ( P =0.405).…”
Section: Discussionmentioning
confidence: 99%
“…Increased activity of ACE-1 in patients with blood group A, higher levels of VWF and Factor VIII, and ABH glycans that modify the affinity of SARS-CoV-2 for ACE-2 receptor or act as an alternative, lower-affinity receptors for the virus can also contribute to the risk of severe COVID-19. 7 Chung et al investigated the association between ABO blood types and ACE activity and showed that individuals with blood type A had the lowest ACE activity, while those with type B had the highest. The mean ACE activity was significantly higher in people with only B antigen compared to blood type O individuals, and significantly lower in blood type A individuals compared to blood type O individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The study found no significant association between the ABO blood group and COVID-19 outcomes except for blood group AB having higher odds of disease severity. 7 Samra et al found that individuals with blood group A had a higher susceptibility and severity, while those with blood group O had a lower risk. 2 However, a retrospective study of 942 hospitalized patients in San Diego County by Hermel et al found no significant association between ABO blood group type and severity outcomes, once confounding variables were accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…Old age, chronic diseases, gender, 19 immunocompromised condition, blood type A (Rh +ve), and other factors are known risk factors for contracting and later developing severe COVID-19. 19 See the studies by Shibeeb and Khan, 20 Abuawwad et al, 21 Turhan et al, 22 and Hafez et al 23 for comprehensive recent reviews on the relationship between the ABO blood system and the Rh factor and their association with COVID-19 infection, susceptibility, and severity. Although the initial virus that caused the first-ever SARS in Hong Kong in March 2003 19 is no longer a concern, the known characteristics of the current SARS-CoV-2 do not appear to disappear quickly, and many countries are now experiencing the second wave of the outbreak.…”
Section: Introductionmentioning
confidence: 99%